Ezh2 Ameliorates Osteoarthritis by Activating TNFSF13B. (3rd February 2020) - Du, Xiaotian; Chen, Yishan; Zhang, Qin; Lin, Junxin; Yu, Yeke; Pan, Zongyou; Sun, Heng; Yuan, Chunhui; Yu, Dongsheng; Wu, Haoyu; Zhang, Xiaoan; Dai, Jun; et al.
ABSTRACT: Epigenetic regulation is highly correlated with osteoarthritis (OA) development, whereas its role and detailed mechanisms remain elusive. In this study, we explored the expression of EZH2, an H3K27me3 transferase, in human OA cartilages and its roles in regulating OA pathogenesis. Here, we found EZH2 was highly expressed in both mice and human OA cartilage samples by using histological analysis and RNA sequencing (RNA‐Seq). The medial meniscectomy (MMx) OA model results indicated the conditional knockout of Ezh2 deteriorated OA pathological conditions. Furthermore, we showed the positive role of Ezh2 in cartilage wound healing and inhibition of hypertrophy through activating TNFSF13B, a member of the tumor necrosis factor superfamily. Further, we also indicated that the effect of TNFSF13B, increased by Ezh2, might boost the healing of chondrocytes through increasing the phosphorylation of Akt. Taken together, our results uncovered an EZH2‐positive subpopulation existed in OA patients, and that EZH2‐TNFSF13B signaling was responsible for regulating chondrocyte healing and hypertrophy. Thus, EZH2 might act as a new potential target for OA diagnosis and treatment. © 2020 American Society for Bone and Mineral Research.